Identification of misfiring in engine 1000cc using fast fourier transform analysis - Erlangga Yorda Agustin; Subekti Subekti; Dayu Andryas Saputra (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
Motorized vehicles are the primary mode of transportation in the neighborhood. An automobile is one of the motorized vehicles. Because of the mixing of air and gasoline, cars may move. The spark plug plays a crucial function in combustion because it ignites the mixture of fuel and air to generate combustion. Incomplete combustion will consequently result in misfiring. Damage to the spark plug, injector, and ignition coil are just a few of the things that might lead to misfiring. Therefore, due to misfiring, research on preventive maintenance for cars is required. Utilizing the vibration approach is one option. The combustion process in this study is stimulated by changing the 1000cc engine's speed. The engine speed ranges from 900 to 3500 revolutions per minute. The accelerometer sensor is then positioned vertically and horizontally on the machine's surface. According to this study, the first form mode's frequency at 900 rpm has an amplitude of 3,433 mm/s2 and occurs at a frequency of 69 Hz. In contrast, the first mode form occurs under typical circumstances at a frequency of 99 Hz and an amplitude of 1,254 mm/s2. Furthermore, at a rotational speed of 2500 rpm, the frequency in the first shape mode is abnormal at 69 Hz with an amplitude of . In contrast, under typical circumstances, the first form mode has a frequency of 249 Hz and an amplitude of 6,721 mm/s2. A frequency of 4x rpm was discovered for the rotational speed parameters of 900 rpm and 2500 rpm. This demonstrates that a misfiring-related bearing issue exists in the piston motor system.